A balancing act: the interaction between the work and personal lives of male and female early career academics - Mitra, M; McAlpine, L (Tyrrell Burgess Associates, 2017)
This qualitative analysis draws upon data from a broader research study that sought to understand early career researchers’ (ECRs) experiences of journeying from post-PhD researcher to independent PI status. A number of unprompted references made by interviewees to their broader lives (i.e., aspects beyond work) when charting their academic trajectories led us to examine this issue more closely. Contrary to existing work, we found that work and family life negotiation is an important concern of both female and male ECRs, although they conceive of it somewhat differently. Our results indicate that there is a need for academic institutions, policymakers, and academe leaders to be attentive to the life issues of both men and women when designing provision for reconciling work and family life in the academic work space.